Civilization and Barbarism in American Literature Vadon, Lehel, ed. To the Memory of Sarolta Kretzoi. Eger: Eszterházy Károly College, 2009. 338 pp. - Ormai, Eszter (FOCUS: Papers in English Literary and Cultural Studies, 2024)
This volume is a collection of essays on American literature and culture dedicated to the memory of the outstanding Hungarian Americanist, Sarolta Kretzoi, who died in 2008. Some of the authors of the essays were her former students who remember her thought-provoking and innovative courses and outstanding organizing activity at the Departments of English and American Literature of various Hungarian universities, in Debrecen, Miskolc, Szeged and Budapest. The first essay recounts her biography and scientific achievements as a university professor and researcher. This is followed by a detailed and complete bibliography of Professor Kretzoi’s monographies and essays.